An American in Paris [videorecording (DVD)] - Lerner, Alan Jay, 1918-1986; Minnelli, Vincente; Kelly, Gene, 1912-1996; Caron, Leslie; Levant, Oscar, 1906-1972 (Warner Home Video, 2008)
An American expatriate painter living in Paris falls in love with an engaged French woman.